2022
DOI: 10.1002/btm2.10369
|View full text |Cite
|
Sign up to set email alerts
|

REverSe TRanscrIptase chain termination (RESTRICT) for selective measurement of nucleotide analogs used in HIV care and prevention

Abstract: Sufficient drug concentrations are required for efficacy of antiretroviral drugs used in HIV care and prevention. Measurement of nucleotide analogs, included in most HIV medication regimens, enables monitoring of short‐ and long‐term adherence and the risk of treatment failure. The REverSe TRanscrIptase Chain Termination (RESTRICT) assay rapidly infers the concentration of intracellular nucleotide analogs based on the inhibition of DNA synthesis by HIV reverse transcriptase enzyme. Here, we introduce a probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…We first tested using CasPART for therapeutic drug monitoring. Measuring antiretroviral drug concentrations in patient samples can enable identification of interindividual differences in drug levels based on missed doses, drug-drug interactions, or differences in drug pharmacokinetics due to age, pregnancy, or body size [55,56]. As a proof-of-concept, we tested measuring rilpivirine, a non-nucleoside reverse transcriptase inhibitor (NNRTI) used in ART regimens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first tested using CasPART for therapeutic drug monitoring. Measuring antiretroviral drug concentrations in patient samples can enable identification of interindividual differences in drug levels based on missed doses, drug-drug interactions, or differences in drug pharmacokinetics due to age, pregnancy, or body size [55,56]. As a proof-of-concept, we tested measuring rilpivirine, a non-nucleoside reverse transcriptase inhibitor (NNRTI) used in ART regimens.…”
Section: Resultsmentioning
confidence: 99%
“…However, prior HIV RT activity assays with PCR-based readout showed that as low as 10% mutant mixed with wild type HIV RT can be detected [62]. The substrate sequence in CasPART could also be systematically designed to match the targeted NRTI drug, to maximize enzyme inhibition events and potentially further favor the detection of MUT RT [56]. Future work is needed to investigate the sensitivity of CasPART in detecting the MUT proportion and optimize assay conditions such as drug concentrations accordingly.…”
Section: Caspart Assay For Phenotypic Characterization Of Hiv Rt Enzymementioning
confidence: 99%